Understanding MPEG-4 - Diepold Klaus; Moeritz Sebastian (Amsterdam Elsevier, 2005)
The Practical Guide to MPEG 4 offers an up to date introduction to this important interactive and multimedia compression standard (including MPEG-4 Part 10), with real examples and information as to how and where this new technology should be used. All a
Keywords: MPEG(Video coding standard)